A SYSTEMATIC ANALYSIS OF SECURITY CHALLENGES IN ENTERPRISE CLOUD DEPLOYMENTS: UNDERSTANDING THE SHARED RESPONSIBILITY MODEL AND RISK MITIGATION STRATEGIES - Ashok Mohan Chowdhary Jonnalagadda (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2024)
This article presents a systematic analysis of critical security challenges in cloud computing deployments, with particular emphasis on the complexities of the shared responsibility model and its implementation across diverse enterprise environments. Through an extensive review of current literature, industry case studies, and empirical data, we investigate the primary security concerns including data breaches, misconfigurations, and regulatory compliance challenges in multi-cloud architectures. The article reveals significant gaps in the interpretation and implementation of security responsibilities between cloud service providers and customers, leading to increased vulnerability risks. The article proposes a comprehensive framework for addressing these challenges, incorporating automated security checks, continuous monitoring mechanisms, and adaptive compliance management strategies. The article further examines the effectiveness of emerging technologies such as AI-driven security monitoring and zero trust architectures in mitigating identified risks. The findings demonstrate that organizations implementing the proposed framework showed a 47% reduction in security incidents and a 62% improvement in compliance adherence. This article contributes to both theoretical understanding and practical implementation of cloud security measures, providing actionable insights for security professionals and technology leaders in managing complex cloud environments.